2023
DOI: 10.1111/rda.14354
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and physiochemical evaluation of buck semen cryopreserved with antioxidants

Abstract: The current study evaluated the physiochemical quality and gene expression profile of post‐thawed buck semen after supplementation with antioxidants [melatonin (M), L‐carnitine (LC), cysteine (Cys), LC + M, M + Cys, LC + Cys, LC + Cys + M] in comparison with the non‐treated control group. Physical and biochemical characteristics of semen were evaluated following freezing and thawing. Transcript abundance of six selected candidate genes was profile using quantitative real‐time PCR. The data demonstrated signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…By considering the supporting role of Nrf2 to spermatogenesis and sperm quality, Sadeghiani et al [99] reported that pentoxifylline supplementation during freezing protocol and long-term storage protected mouse spermatogonial stem cell activating the antioxidant defense through the Nrf2/ARE signaling pathway. In addition, the transcription of NRF2, together with that referred to SOD1 and GPx1, was up-regulated in post-thawed buck semen after supplementation with antioxidants [100].…”
Section: Role Of Nrf2 In Long-term Storage Of Spermmentioning
confidence: 96%
“…By considering the supporting role of Nrf2 to spermatogenesis and sperm quality, Sadeghiani et al [99] reported that pentoxifylline supplementation during freezing protocol and long-term storage protected mouse spermatogonial stem cell activating the antioxidant defense through the Nrf2/ARE signaling pathway. In addition, the transcription of NRF2, together with that referred to SOD1 and GPx1, was up-regulated in post-thawed buck semen after supplementation with antioxidants [100].…”
Section: Role Of Nrf2 In Long-term Storage Of Spermmentioning
confidence: 96%